Inclusão e exclusão na sociedade moderna: uma visão sistêmica sobre o acesso à educação média no Brasil - Blecher, Carlos Henrique de Oliveira (2008)
Relying on Luhmann s systems theoretical observation on modern society, this dissertation aims, having the basic education reality in Brazil as an empirical model, at questioning the basic systemic theoretical notions of the current debate on the distinction inclusion/exclusion. After presenting the main aspects of Luhmann s theory on modern society, mainly the system of law and its relation to education system, this work will try to assess the most remarkable aspect of Luhmann s concept of the inclusion/ exclusion relationship within a new reality of functionally differentiated society, in which individuals are not only situated out of society but also, to be precise, within its the exclusion domain. In that way, Luhmann has put lights on some fundamental issues regarding the implicit norm of full inclusion, which seems to be the main focus relied on inclusion/exclusion debate nowadays. Following this new path, Luhmann also directs his attention to the different conditions of inclusion/exclusion as being surrounded and here it is really important to map the theoretical ground out by conditions within function systems, organization and interaction systems. Luhmann s point of view comes down to the idea that inclusion is not the rule anymore, by contrast, exclusion is. This work closes off with a critical analysis of Luhmann s re-description of the quoted distinction and, raising the reality of basic educational access in Brazil, considering, moreover, the quality of it, suggests that the system theory might suffer from an empirical deficiency. In the present work, once having the figures on educational inclusion/exclusion in Brazil and its further developments exposed, we come across the fact that the system theory seems to have difficulties to grasp and to depict the actual mechanisms of social exclusion in the world